2018
DOI: 10.2478/sbe-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Do Natural Disasters Cause Economic Growth? An ARDL Bound Testing Approach

Abstract: This article strives to work out the causal relationship between natural disasters and economic growth in Pakistan. The study empirically tests the linkage using econometric techniques autoregressive distributed lag bound model by Pesaran (2001) and Granger causality test. We develop a proxy for the loss of natural disasters by a similar method as Noy (2009) and Bergholt et.al, (2012) did. The results of ARDL bounds testing approach evidence a negative long run relationship between the proxies of natural disas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The presence of unidirectional causality running from natural disasters to economic growth in this study is supported by similar findings in other countries prone to natural disasters, such as Pakistan [31], Philippines [32], and India [33]. Furthermore, previous studies conducted in developing countries have found unidirectional causality from natural disasters to GDP per capita, while this relationship is not observed in developed countries [34].…”
Section: Results Of Multivariate 'Vecm' Causalitysupporting
confidence: 88%
“…The presence of unidirectional causality running from natural disasters to economic growth in this study is supported by similar findings in other countries prone to natural disasters, such as Pakistan [31], Philippines [32], and India [33]. Furthermore, previous studies conducted in developing countries have found unidirectional causality from natural disasters to GDP per capita, while this relationship is not observed in developed countries [34].…”
Section: Results Of Multivariate 'Vecm' Causalitysupporting
confidence: 88%
“…For example, Shabnam [ 39 ] reported 0.005% decline in GDP/capita for one thousand out of one million population disturbed by floods in 187 countries. The economic damage is also reported in 171 countries [ 118 ], 21 Caribbean countries [ 42 ], and Pakistan [ 41 ]. Another study [ 25 ] reported that severe natural disasters showed an adverse impact on economic growth (−0.016), fiscal balance (−0.011), and FDI (−0.0271) in the B&RIC.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is located in an extreme risk zone in terms of natural disasters. Due to this, Baig et al [ 41 ] explained the causality between economic growth and natural disasters in Pakistan. The results confirmed an inverse link between economic growth and natural disaster loss.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 1800 people lost their lives in the recent disaster, and there were tens of billions of dollars in financial losses. Between independence in 1947 and the 2010 flooding, nearly 8000 people perished, and economic damages totaled $10 billion, according to the most recent official statistics (Baig, et al, 2018). These estimates are made at the local administrative level, and it is unknown how accurate they are.…”
Section: Flood Managementmentioning
confidence: 99%